Impositions, Resistances and Counter-Resistances: The Application of the Criminal Code of the Helvetic Republic in Ticino (1799-1803) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2025)
The criminal code of the Helvetic Republic, which was activated throughout the territory of the Republic in May 1799 and abolished following the Act of Mediation (February 1803), was the first penal code with which the courts in Ticino, despite themselves, had to deal. On the basis of the criminal acts produced by the latter and moving from the concept of ‘internal frontier’, the contribution proposes a reflection on this moment of rupture in Swiss and Ticino’s history, between the ancient regime and the Napoleonic era: a time when Ticino can be read as a sort of ‘laboratory’ in which local legal traditions on the one hand, and the Enlightenment and revolutionary currents on the other, met, clashed, or ignored each other – with various shades of permeability, influence and resistance.
Keywords: Helvetic Republic, Ticino, Mediation, criminal trial, torture, legal profession